Development of a web platform for COVID-19 integrated care: an experience from an Italian Region. (20th October 2021) - Di Martino, G; Di Biagio, R; Soldato, G; Del Papa, J; Porfilio, I; Stella, A; Polidoro, I; Fabiani, L; Caponetti, A; Ruotolo, L
Abstract: Issue: After the announcement of Public Health Emergency of International Concern about COVID19 by WHO, health authorities need to implement strategies to face the emergency. These responses included early diagnosis, patient isolation, quarantine and symptomatic monitoring of contacts. In this context, integrated care and telemedicine are the best instruments for COVID management. Description of the problem: The COVID19 epidemic needs a real time integration of epidemiological, clinical and laboratoristic data, in order to better manage patients and to improve public health surveillance. Based on a tool previosly used by GPs for flu vaccination and diabetes integrated care, the Local Health Authority of Pescara, Abruzzo Region, Italy, developed a web-based platform (QuickwebConnect), accessible to public health practitioners (PHP), GPs, infectious diseases physicians and laboratories, in order to integrate information about COVID19 patients. This platform contain individual-level information on patients with laboratory-confirmed COVID19, symptoms, reported onset dates, and basic demographics. Information are in real time accessible to all actors involved in the process. In addition, GPs can use this tool to directly book diagnostic tests for symptomatic or suspected patients. Results: With the use of this platform, the management of pandemic emergency was improved, allowing direct management of epidemic data both at person and population level. The real time evaluation of clinical and epidemiological data improved patients care, clinical survellance of COVID19 contacts and development of tailored preventive measure in areas with high incidence. Lessons: COVID19 patients care need to be quick, needing the integrate support of different actors. In addition, public health actions have to be supported by strong data. The use of a cost-effective web platform allow physician and PHP to better manage patiens and develope focused interventions. Key messages: Integrated care and telemedicine are best instruments for COVID management. The real time evaluation of data aimed to develop tailored preventive measure.